Mortality Benefit of Participation in BOOCS Program: A Follow-Up Study for 15 Years in a Japanese Working Population. Issue 3 (March 2015) - Hoshuyama, Tsutomu; Odashiro, Keita; Fukata, Mitsuhiro; Maruyama, Toru; Saito, Kazuyuki; Wakana, Chikako; Fukumitsu, Michiko; Fujino, Takehiko
Abstract : Objective: This study aims to demonstrate the protective effect on mortality among participants of a health education program, Brain-Oriented Obesity Control System (BOOCS). Methods: A quasi-experimentally designed, 15-year (1993 to 2007) follow-up study was conducted with a total of 13, 835 male and 7791 female Japanese workers. They were divided into three groups: participants in the program (1565 males and 742 females), nonparticipant comparative obese controls (1230 males and 605 females), and nonparticipant reference subjects (11, 012 males and 6426 females). Hazard ratios were calculated with survival curves drawn to evaluate the mortality effects by the program participation. Results: The male participants showed significantly lower mortality risk for all causes of death at hazard ratio = 0.54 (95% confidence interval: 0.31 to 0.94) with significantly different survival curves ( P = 0.014 by log-rank test) than obese controls. Conclusions: The results support a protective effect on mortality by participating in BOOCS program.